Penyusunan Program Legislasi Daerah yang Partisipatif - Sunarno Danusastro (Jurnal Konstitusi, 2016)
This research studies and answers the problem concerning the development of participatory Local Legislation Program. In addition it also aims to find out the role of Local Government in developing a participatory Local Legislation Program.This study was a non-doctrinal or empirical law research that was exploratory in nature. The research was taken place in Surakarta. The types of data used were primary and secondary data. The primary data source was obtained from the result of interview with the Meeting and Legislation Division of Surakarta City’s Local Legislative Assembly, Law and Human Right Division of Surakarta City Government, Non Government Organization, and Political Parties related to the development of participatory Local Legislation Program. The secondary data source  derived from the law materials involving primary, secondary, and tertiary law materials. Techniques of collecting data used were interview and library study from the books, legislations, documents, and etc. The data analysis was done using an interactive model of qualitative analysis starting with data collection, then data reduction, data display, and finally conclusion drawing.To make a description and perception on the problem, the local government, local legislation, and democratic theories. From the discussion of research result, the following conclusion could be drawn: Democracy is a part of  constitutional state of Indonesia characterized by among other community participation in the government as the form of people sovereignty. In the process of developing Local Regulation, the participatory Local Legislation Program occupies a very important position because it can become the reference concerning the scale of Local Regulation draft development priority for 1-year period corresponding to the mandate of Act Number 12 of 2011 about the Legislation Development. For that reason, the local government, in this case Municipal Government and Local Legislative Assembly as the holder of authority of developing Local Legislation Program should pass through the participatory mechanism by involving the people and stakeholders such as Non Government Organization so that the Local Legislation Program yielded was the aspiratory and participatory proposals of Local Regulation Draft and in practice, such the proposals of Local Regulation Draft was developed in planned, integrated and systematic manner.